PENIDIKAN ANAK BERBAKAT DAN PERAN REGULASI DIRI DALAM MENCEGAH BURNOUT - Dina Mariana Siregar; Zimri Maritza; Shania Inseri Simyapen (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Gifted children often face intense academic and social pressures, which can lead to burnout if not manages properly. This article aims to review the literature on educational approaches fot gifted children and highlight the role of self regulation as a protective mechanism against burnout. Through a literature review of national sources, it was found that adaptive aducational strategies and strengthening emotional regulation skills can halp giftes children manage stress and achieve their optimal potential. The purpose of this study is to determine how important the role of self-regulation is in preventing burnout.